Apolipoprotein E ε4 Is Associated With the Development of Incident Dementia in Cerebral Autosomal Dominant Arteriopathy With Subcortical Infarcts and Leukoencephalopathy Patients With p.Arg544Cys Mutation - Lee, Jung Seok; Ko, Keun Hyuk; Oh, Jung-Hwan; Kim, Joong-Goo; Kang, Chul-Hoo; Song, Sook-Keun; Kang, Sa-Yoon; Kang, Ji-Hoon; Park, Joon Hyuk; Koh, Myeong Ju; Lee, Ho Kyu; Choi, Jay Chol (Frontiers in Aging Neuroscience, 2020)
Background and Purpose: To identify clinical, laboratory, and magnetic resonance imaging (MRI) features in predicting incident stroke and dementia in Korean patients with CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy). Materials and methods: We enrolled 87 Korean CADASIL patients who had undergone baseline clinical, laboratory, and MRI examination between March 2012 and February 2015. The primary outcome of this study is the occurrence of stroke and dementia during the study period. Occurrence of incident stroke was confirmed by neuroimaging study and dementia was defined by the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) criteria. Results: Of the 87 patients, 57.5% were men and the mean age was 63±13 years (range 34–90) and 82 patients (94.3%) had p.Arg544Cys mutation. During average follow-up of 67 months (interquartile range: 53–69 months), incident stroke occurred in 14 of 87 patients (16.1%), and incident dementia in 7 of 70 non-demented patients (10.0%). In adjusted analysis, increased systolic blood pressure was associated with increased risk of incident stroke (for every 10mmHg increase; hazard ratio [HR], 1.44 [1.02–2.03]). Apolipoprotein E (APOE) ε4 genotype was associated with increased risk of incident dementia (HR, 10.70 [1.27–89.88]). Conclusion: In this study, APOE ε4 genotype was associated with the development of incident dementia, and higher blood pressure was associated with increased risk of incident stroke in CADASIL patients with predominant p.Arg544Cys mutation.